2021
DOI: 10.5194/acp-21-12413-2021
|View full text |Cite
|
Sign up to set email alerts
|

Observation and modelling of ozone-destructive halogen chemistry in a passively degassing volcanic plume

Abstract: Abstract. Volcanoes emit halogens into the atmosphere that undergo complex chemical cycling in plumes and cause destruction of ozone. We present a case study of the Mount Etna plume in the summer of 2012, when the volcano was passively degassing, using aircraft observations and numerical simulations with a new 3D model “WRF-Chem Volcano” (WCV), incorporating volcanic emissions and multi-phase halogen chemistry. Measurements of SO2 – an indicator of plume intensity – and ozone were made in the plume a few tens … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(59 citation statements)
references
References 86 publications
9
50
0
Order By: Relevance
“…Here we introduced Br2 as a new species and its photolysis (R7) and gas-phase reaction with OH. Additionally, we included the 3 heterogeneous reactions (R5a), (R5b) and (R6) and 6 halogen gaseous reactions following Surl et al (2021). The Supplement gives the list of the halogen species and reactions present in the updated version of MOCAGE chemistry and details on the calculation of the heterogeneous reactions.…”
Section: Model Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here we introduced Br2 as a new species and its photolysis (R7) and gas-phase reaction with OH. Additionally, we included the 3 heterogeneous reactions (R5a), (R5b) and (R6) and 6 halogen gaseous reactions following Surl et al (2021). The Supplement gives the list of the halogen species and reactions present in the updated version of MOCAGE chemistry and details on the calculation of the heterogeneous reactions.…”
Section: Model Descriptionmentioning
confidence: 99%
“…As discussed above, there is not a full understanding of the processes occurring when magmatic air first mixes with atmospheric air at high temperature. Previous studies showed that the choice of this composition is important at fine scale resolutions (Roberts et al, 2009;Roberts et al 2014, Jourdain et al, 2016Surl et al, 2021). Here, we will investigate this issue at a coarser horizontal resolution that is typical of the 3D MOCAGE simulations.…”
mentioning
confidence: 98%
“…Mount Etna is one of the most important continuous emitters of gases such as H 2 O, SO 2 and less reactive carbon dioxide [106,107], hydrogen sulphide (H 2 S) [108], and volcanic bromine monoxide (BrO) [109][110][111], as well as high-temperature volcanic products such as Br, OH and NO [110,112]. In a natural volcanic environment, within minutes of emission, primary volcanic plume aerosols catalyze the conversion of co-emitted HBr and HCl into the highly reactive halogens BrO and OClO (chlorine dioxide) through chemical cycles, which cause substantial ozone depletion within the dispersing downwind plume [111,113].…”
Section: Chemical Sources Of Sulfuric Acidmentioning
confidence: 99%
“…In a natural volcanic environment, within minutes of emission, primary volcanic plume aerosols catalyze the conversion of co-emitted HBr and HCl into the highly reactive halogens BrO and OClO (chlorine dioxide) through chemical cycles, which cause substantial ozone depletion within the dispersing downwind plume [111,113]. These chemical processes increase the atmospheric lifetime of SO 2 and decrease sulfuric production [112,114]. The sources of the above-mentioned overestimation of (H 2 SO 4 ) in our simulations could be the lack of some key volcanic species in model settings such as halogens, or near-vent high-temperature products, such as OH and Br [112,115].…”
Section: Chemical Sources Of Sulfuric Acidmentioning
confidence: 99%
See 1 more Smart Citation